(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
In our century, which is developing day by day, it is difficult to imagine our life without modern technologies. The orientation of these technologies to the education system helps to make the process of educating students more effective, interesting and interactive. Modern information and communication tools, digital platforms are being used effectively and widely in teaching all subjects at school and university levels. One of the reasons for this is that, while in traditional education, students were taught only to acquire ready-made knowledge, modern technologies teach them to search for the knowledge they acquire themselves, to study and analyze it independently, and even to draw conclusions on their own. Therefore, studying the role of modern tools in the teaching process and their effectiveness is one of the urgent issues in today’s educational environment. In this regard, at a videoconference meeting on improving the public education system and raising the spirituality of the younger generation, which was held under the chairmanship of the President of the Republic of Uzbekistan Shavkat Mirziyoyev, he expressed some thoughts based on technological education: "It is necessary to create a modern and rational system in the field of education, to update teaching methods, educational standards, textbooks and study guides."